Journal of the National Sample Survey Organisation Vol. I No. 2 October 1977 - Planning Commission (Planning Commission, 1977)
The economic condition of the weaker section of rural population comprising the small cultivator and non-cultivating wage earner households and their attitude towards the prospects of an improvement of their economic conditions through governmental measures are examined. The problem of underutilisation of labour force in terms of additional employment that would be needed for ensuring the minimum level of living of the weaker section is also discussed.
Department of Statistics, Ministry of Planning, Government of India